Corneal topography and tomography readings with mask wear during the COVID-19 pandemic. Issue 3 (16th March 2023) - Zein, Mike; Wylegala, Adam; Sripawadkul, Wathanee; Al Bayyat, Ghada; Alvarez, Osmel P.; Gutierrez, Alejandro J.; Guerrero, Miguel A.; Galor, Anat; Karp, Carol L.
Abstract : This study assessed the impact of mask wear on corneal keratometry readings. More than half of the subjects had a >10 degree change in axis of astigmatism with mask wear. Abstract : Purpose: To assess the effect of mask wear on corneal topography and tomography readings. Setting: Tertiary ophthalmic center. Design: Prospective, observational, comparative study. Methods: Subjects underwent imaging with the Tomey TMS-4a topographer and the Oculus Pentacam HR tomographer. Imaging was performed without a mask, and then testing was repeated while wearing 3 different masks: Halyard Level 2, Halyard Level 3, and KN95. Measurements during mask wear were compared with measurements without a mask. The Kruskal-Wallis analysis of variance grouped test was used to compare mean differences without vs with mask wear on measurements. The Chi-square test was used to compare frequency of differences between different masks and against-the-rule vs with-the-rule astigmatism. The frequencies of clinically significant changes in axis of astigmatism, magnitude of astigmatism, and mean keratometry (K) values were calculated. Results: 52 eyes were included in the study with a mean age of 34.71. Mask wear did not show statistically significant differences in mean topography and tomography measurements compared with without mask wear for all parameters. However, the majority, 53% (83/156) had a >10 degrees and 41% (64/156) had >15 degrees change in axis of astigmatism on topography when wearing a mask compared with no mask wear. Conclusions: Mask wear did not result in statistically significant mean changes in K readings on topography and tomography. However, the axis of astigmatism varied >10 degrees in most of the patients. Axis determination should be interpreted with caution regarding refractive surgery and/or toric intraocular lens planning in individuals whose measurements were obtained while wearing a mask.